EXPERIMENTAL STUDY OF HEAT TRANSFER OF PALM OIL AS WORKING FLUID FROM PARABOLIC TROUGH SOLAR COLLECTOR INSTALLED IN GUNUNG KIDUL YOGYAKARTA - Joko Purwanto, Andri
The consumption of energy in the world will increase because of the development of technology. Fossil fuel that has been the largest energy source in the world existence is diminishing. Solar is one of the alternative energy sources that can be utilized to replace energy from fossils. The availability of solar energy is very abundant, because almost everywhere in the world is illuminated by solar. It is encourages to research on the utilization of solar energy in many countries, and competing to gain the advantage from more efficient solar energy. One of solar energy utilization is through Solar Thermal Collector (STC) which has the principle of transferring solar thermal energy and collect it into a particular media. Parabolic Trough Solar Collector (PTSC) with line focussing type is one of concentrating collector type with length of 18 m, width of 3,5 m and a focal distance of 1 m. It is used to heat palm oil as working fluid that flows in the absorber at focal line of PTSC. The PTSC prototype installed in Gunung Kidul Yogyakarta is a research facility owned by the Indonesian Institute of Sciences. The results obtained from the experiment were the increase in working fluid temperature of 8°C for 7 hours of collector heating. The average input energy is 1170061,2 kJ with an average solar intensity of 737.7 W/m2. The energy absorbed by the palm oil is 20139 kJ.